A step towards removing plasma volume variance from the Athlete's Biological Passport: The use of biomarkers to describe vascular volumes from a simple blood test. Issue 2 (27th July 2017) - Lobigs, Louisa M.; Sottas, Pierre‐Edouard; Bourdon, Pitre C.; Nikolovski, Zoran; El‐Gingo, Mohamed; Varamenti, Evdokia; Peeling, Peter; Dawson, Brian; Schumacher, Yorck O.
Abstract : The haematological module of the Athlete's Biological Passport (ABP) has significantly impacted the prevalence of blood manipulations in elite sports. However, the ABP relies on a number of concentration‐based markers of erythropoiesis, such as haemoglobin concentration ([Hb]), which are influenced by shifts in plasma volume (PV). Fluctuations in PV contribute to the majority of biological variance associated with volumetric ABP markers. Our laboratory recently identified a panel of common chemistry markers (from a simple blood test) capable of describing ca 67% of PV variance, presenting an applicable method to account for volume shifts within anti‐doping practices. Here, this novel PV marker was included into the ABP adaptive model. Over a six‐month period (one test per month), 33 healthy, active males provided blood samples and performed the CO‐rebreathing method to record PV (control). In the final month participants performed a single maximal exercise effort to promote a PV shift (mean PV decrease −17%, 95% CI −9.75 to −18.13%). Applying the ABP adaptive model, individualized reference limits for [Hb] and the OFF‐score were created, with and without the PV correction. With the PV correction, an average of 66% of [Hb] within‐subject variance is explained, narrowing the predicted reference limits, and reducing the number of atypical ABP findings post‐exercise. Despite an increase in sensitivity there was no observed loss of specificity with the addition of the PV correction. The novel PV marker presented here has the potential to improve the ABP's rate of correct doping detection by removing the confounding effects of PV variance. Abstract : Plasma volume (PV) shifts represent a major confounding factor within the Athlete's Biological Passport (ABP) reference limit calculations for concentration‐based haematological markers, haemoglobin concentration ([Hb]) and the OFF‐score. A newly developed PV marker (comprising eight common chemistry variables, from a simple blood test) is capable of removing 66% of [Hb] within‐subject variance, narrowing the predicted reference limits for [Hb] and the OFF‐score and also allowing for PV fluctuations. This approach has the potential to improve the ABP's rate of correct doping detection by removing the confounding effects of PV variance.